Luteolin combined with low‐dose paclitaxel synergistically inhibits epithelial–mesenchymal transition and induces cell apoptosis on esophageal carcinoma in vitro and in vivo. (7th September 2021) - Qin, Tiantian; Zhao, Jinzhu; Liu, Xiaojie; Li, Leilei; Zhang, Xueyan; Shi, Xiaoli; Ke, Yu; Liu, Weihua; Huo, Junfeng; Dong, Yalong; Shen, Yiwei; Li, Yanyu; et al.
Abstract : Although paclitaxel is a promising frontline chemotherapy agent for various malignancies, the clinical applications have been restricted by side effects, drug resistance, and cancer metastasis. The combination of paclitaxel and other agents could be the promising strategies against malignant tumor, which enhances the antitumor effect through synergistic effects, reduces required drug concentrations, and also suppresses tumorigenesis in multiple ways. In this study, we found that luteolin, a natural flavonoid compound, combined with low‐dose paclitaxel synergistically regulated the proliferation, migration, epithelial–mesenchymal transition (EMT), and apoptosis of esophageal cancer cells in vitro, as well as synergistically inhibited tumor growth without obvious toxicity in vivo. The molecular mechanism of inhibiting cell migration and EMT processes may be related to the inhibition of SIRT1, and the mechanism of apoptosis induction is associated with the reactive oxygen species (ROS)/c‐Jun N‐terminal kinase (JNK) pathway–mediated activation of mitochondrial apoptotic pathway.